From proto-Kranz to C4 Kranz building the bridge to C4 photosynthesis - Sage, Rowan F (Journal of experimental botany, 2014)
© The Author 2014. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.